Empirical and numerical assessment of two extended stopes for dilution estimation in an underground mine - Santos Chauca, AI; Shnorhokian, S; Kumral, M (Deep Mining 2024: Proceedings of the 10th International Conference on Deep and High Stress Mining, 2024)
Over the decades, several empirical and analytical approaches have been developed to assess the stability of underground excavations. For stope design, the stability graph method is commonly used for preliminary sizing assessments. The method has been modified by multiple authors over time using extensive databases to adjust the three factors and boundary limits for the stability zones. Based on field observations, the adjustments were made to improve the qualitative representation of rock mass stability and associated risks. Moreover, different applications such as the dilution graph have been developed based on the stability graph method. The overbreak prediction for open stope footwalls and hanging walls can be quantified with this graph. Numerical modelling is another important tool in rock engineering, commonly utilised in conducting complex analyses in mining. The model consists of numerous elements or zones that discretise the rock mass, requiring initial calibration to predict future results. In the stability graph method, the estimation of induced stress for the stability Factor A purely depends on numerical analysis techniques. In the present study, an assessment is developed for the stability of two extended stopes that were extracted in an underground mine. The stope designs were evaluated using the stability graph method and two versions of the dilution graph. Advanced 3D models were constructed for determining Factor A and for assessing the stability of stope surfaces based on a numerical approach. Finally, a comparison was made between the empirical results of the stability graph method and dilution graph, the numerical models, and actual field observations and cavity monitoring survey (CMS) measurements after the extraction of each stope at the mine.
Keywords: ore dilution